2005
DOI: 10.1002/sia.2062
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of wet-etched GaAs (100) surfaces

Abstract: To enable the use of GaAs-based devices as chemical sensors, their surfaces must be chemically modified. Reproducible adsorption of molecules in the liquid phase on the GaAs surfaces requires controlled etching procedures. Several analytical methods were applied, including Fourier transform infrared spectroscopy (FTIRS) in attenuated total reflection and multiple internal reflection mode (ATR/MIR), high-resolution electron energy loss spectroscopy (HREELS), X-ray photoelectron spectroscopy (XPS) and atomic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 26 publications
6
74
1
Order By: Relevance
“…Liquid samples analysis is considered complimentary to previously reported XPS data and overall data interpretation was based on previously concluded ability of HF and HCl acids to efficiently remove native oxides. [9][10][11] One minute experiments showed that concentrated HF and diluted HCl may leave surface As-rich, while diluted ammonia hydroxide removes In at a slower rate than As and Ga. 30 minute experiment further confirmed observations for concentrated HF, diluted HCl and ammonia hydroxide. Diluted citric acid demonstrated more uniform InGaAs surface layer removal at both 1 minute and 30 minutes exposure.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Liquid samples analysis is considered complimentary to previously reported XPS data and overall data interpretation was based on previously concluded ability of HF and HCl acids to efficiently remove native oxides. [9][10][11] One minute experiments showed that concentrated HF and diluted HCl may leave surface As-rich, while diluted ammonia hydroxide removes In at a slower rate than As and Ga. 30 minute experiment further confirmed observations for concentrated HF, diluted HCl and ammonia hydroxide. Diluted citric acid demonstrated more uniform InGaAs surface layer removal at both 1 minute and 30 minutes exposure.…”
Section: Resultssupporting
confidence: 58%
“…[7][8][9][10] Nitric acid also acts as a strong oxidizer and thus achieves high etch rates. We suggested a simplified scheme for describing the etching mechanism where two processes of oxidation and oxide etching need to be happening simultaneously in order to achieve etching of bulk III-V layers.…”
Section: Resultsmentioning
confidence: 99%
“…These films are usually stable, yet they can be chemically etched. [18,19] The reports on GaAs native oxides are inconsistent in their compositional analyses; for example, the Ga/As ratios vary significantly and appear to depend both on instrumentation and the etchant used. [20 -23] Furthermore, not all oxidation states of Ga and As were correctly identified by XPS.…”
Section: Introductionmentioning
confidence: 99%
“…[26] The need to develop a reliable method for passivating GaAs surfaces was realized long ago. [27] It is especially important for any in vivo application, in which one has to protect the GaAs surface and prevent toxic arsenic compounds from getting in contact with living systems.…”
Section: Mocser-based Biosensorsmentioning
confidence: 99%